2012
DOI: 10.4161/epi.21180
|View full text |Cite
|
Sign up to set email alerts
|

Methylation changes atNR3C1in newborns associate with maternal prenatal stress exposure and newborn birth weight

Abstract: Early life experiences, including those in utero, have been linked to increased risk for adult-onset chronic disease. The underlying assumption is that there is a critical period of developmental plasticity in utero when selection of the fetal phenotype that is best adapted to the intrauterine environment occurs. The current study is the first to test the idea that extreme maternal psychosocial stressors, as observed in the Democratic Republic of Congo, may modify locus-specific epigenetic marks in the newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
230
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(253 citation statements)
references
References 16 publications
(21 reference statements)
17
230
0
6
Order By: Relevance
“…Our findings suggested that maternal PTSD could delay the physical and behavioral development of offsprings, with evidence of lowered body weight and poorer performance in OFT testing, consistent with a previous report (Zhang et al, 2012). Mulligan et al (2012) reported that extreme maternal psychosocial stress stimulation could alter locus-specific epigenetic marks in neonate and found significant correlations among maternal prenatal stress, birth weight, and promoter methylation of the glucocorticoid receptor NR3C1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings suggested that maternal PTSD could delay the physical and behavioral development of offsprings, with evidence of lowered body weight and poorer performance in OFT testing, consistent with a previous report (Zhang et al, 2012). Mulligan et al (2012) reported that extreme maternal psychosocial stress stimulation could alter locus-specific epigenetic marks in neonate and found significant correlations among maternal prenatal stress, birth weight, and promoter methylation of the glucocorticoid receptor NR3C1.…”
Section: Discussionsupporting
confidence: 91%
“…A growing body of evidence has suggested that maternal PTSD and other stressors also influence the behavioral development and hormone levels of offsprings (Mulligan et al, 2012). Maternal PTSD contributes to alterations in the stress-induced responsivity of the HPA axis; the transportation and distribution of regulatory neurotransmitters, such as dopamine, acetylcholine, and serotonin; the modification of key limbic structures; and the retardation of intrauterine growth (Kofman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Gestational dysregulation of the HPA axis, and of NR3C1 in particular, has been implicated in the pathophysiology of major neurobehavioral disorders. 36 Most studies considering gestational influences for NR3C1 methylation have focused on maternal psychosocial factors, such as depression, 37 stress 5 and trauma 38 during pregnancy, given the potential for such exposures to directly overload and disrupt developing stress-response systems. No human studies have considered the role of neurotoxic metals as similarly disrupting NR3C1, despite the evidence linking prenatal metals exposure to a similar set of at-risk neurobehavioral phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DNA methylation levels at the IGF2 gene were reported to be significantly lower in adults who were in utero during the Dutch Hunger Winter Famine (1944Famine ( -1945) when compared to same-sex siblings in utero unexposed to famine (Heijmans et al, 2008). Other candidate gene studies have also reported birth weight related methylation differences in imprinted genes that play a role in fetal growth, such as IGF2 and H19 (Hoyo et al, 2012;Steegers-Theunissen et al, 2009) and in nonimprinted genes such as the glucocorticoid receptor NR3C1 (Filiberto et al, 2011;Mulligan et al, 2012). More recently, epigenome-wide association studies (EWAS) have been performed for birth weight using the Infinium HumanMethylation27 BeadChip (Infinium 27K; Adkins et al, 2012;Banister et al, 2011;Fryer et al, 2011;Straughen et al, 2015) and the Infinium HumanMethylation450 BeadChip (Infinium 450K; Engel et al, 2014;Simpkin et al, 2015) methylation platforms (Illumina Inc, San Diego, CA).…”
mentioning
confidence: 99%